The Effect of Content and Language Integrated Learning on Reading Comprehension at Eleventh Grade at SMA Al-Ijtihad In Academic Year 2018/2019 - Nurul Islami Dewi; Imam Sudarmaji (Teacher Training and Education Faculty of Syekh-Yusuf Islamic University Tangerang, 2020)
ABSTRACT This research aims at finding out the effect of Content and Language Integrated Learning (CLIL) strategy at eleventh grade of SMA Al-Ijtihad Kota Tangerang. This research was quantitative with the quasi-experimental to chose the sample, and got 57 students to two classes : one experimental and one control. The experimental class (XI IPS 2) which was taught by Content and Language Integrated Learning (CLIL) strategy, whereas the control class (XI IPS 1) which was taught by Conventional Instruction (CI). The researcher used the written test to collect the data, and counting the data with the chi square formula to test normality data, fisher formula to test homogeneity data. The result of this research showed the students' score of reading comprehension after taught by Content and Language Integrated Learning (CLIL) is good, because the mean value of post-test which was taught by is Content and Language Integrated Learning (CLIL) higher than students which was taught by Conventional Instruction (CI). So, the gained results of the research indicated that Content and Language Integrated Learning (CLIL) strategy is an effective strategy on improving students' reading comprehension, however there are some constraints on the language used by the researchers in this strategy, namely the use of English to convey the material.